Taxonomic revision of Australian long-horn moths of the genus Nemophora (Lepidoptera: Adelidae) - Kozlov, Mikhail V. (Zootaxa, 2016)
The taxonomic revision of Australian species of the genus Nemophora Hoffmannsegg is based on investigation of type materials of all described taxa. Lectotypes are designated for Nemotois opalina Meyrick, 1912; N. panaeola Turner, 1913; N. sparsella Walker, 1863; N. topazias Meyrick, [1893]; N. orichalcias Meyrick, [1893]; and N. selasphora Turner, 1913. N. topazias Meyrick, syn. nov. and N. selasphora Turner, syn. n. are synonymized with Nemophora laurella (Newman, 1856). Two new species, Nemophora doddi sp. nov. and N. turneri sp. nov., are described from Queensland. The fauna of Australia currently includes seven valid species of Nemophora, which form a monophyletic laurella species-group. Keys to species based on external characters and on male genitalia are provided; adults and male genitalia are described and illustrated.